The Implementation of Metacognition in Teaching Character Education in Primary Education - Elisabeth Avryanne Suminto; Concilianus Laos Mbato (Institut Agama Islam Negeri Palopo, 2020)
Metacognition is concerned with a person’s awareness of his or her own thinking processes. It is essential to study the implementation of metacognition in teaching character education since it serves as the basis for the teachers to guide the students into holistic learning. This research focused on the teachers’ perceptions on the implementation of metacognition in character education. In particular, it aimed to obtain the information about the extent to which metacognition in character education in primary education led the teachers to school vision. The researchers employed mixed-method research involving twenty-one primary school teachers in a primary school in the Magelang region, Central Java. The instrument used were questionnaire and interview. The findings of this research showed that the teachers perceived the implementation of metacognition in teaching character education positively. However, the results of the interview revealed that they did not implement regulation of cognition wholly. Furthermore, the results of the open-ended questionnaire showed that there were four values which were well-implemented i.e., compassion, celebration, competence, and conviction. For the future research, therefore, urges future researchers to conduct a research in the broader scope of schools.